Combined Effects of Humic Acid-Modified Magnetic Biochar and AMF on the Properties of Saline-Alkali Soil and Photosynthetic Parameters of Muskmelon - ZHANG Yating; LOU Xueyi; WU Jiarui; LIU Hongyuan; YE Binyu; XIAO Jiamin; LI Jiameng; MIAO Yining; CHEN Xinyan; LIU Yilin; TAN Yuyu; WANG Zhichao; et al. (Shuitu Baochi Xuebao)
[Objective] To improve humic acid-modified magnetic biochar (HA-MBC) and explore the combined effects of modified biochar and arbuscular mycorrhizal fungi (AMF) on the properties of saline-alkali soils and the growth of muskmelon. [Methods] Through response surface methodology, the effects of the ratio of magnetic biochar to humic acid (1∶4, 1∶6, 1∶8), the concentration of FeCl3 and FeSO4 reagents (0.02, 0.04, 0.06 g/mL), and the cross-linking duration (48, 72, 96 h) on HA-MBC were analyzed, to procure the optimum amendment scheme suitable for combined application with AMF. Moreover, by conducting pot experiments, the influence of individual fungi, individual biochar, and combined biochar-fungi (AMF+10%B, AMF+20%B) on the physicochemical properties, and enzyme activities of saline soil and alkaline soil, and the photosynthetic parameters of muskmelon were studied. [Results] Under 15 and 75 mmol/L saline-alkali stress, combined application of 20 g/kg AMF with 20% HA-MBC showed the best mitigation effects, with a “synergistic enhancement” observed. On one hand, the iron oxides and humic acids loaded on HA-MBC improved the physical and chemical properties of soil by increasing the quantity of surface functional groups and porosity, while AMF formed symbiotic roots to further enrich organic matter and nutrients, and increase soil enzyme activities, thus increasing the height and root length of muskmelon and promoting the recovery of Fv/Fm and the reduction of F0 and qN. On the other hand, the application of HA-MBC could increase the colonization rate of AMF in saline and alkaline soils by 19.46% and 22.72%, respectively, thus further enhancing the effects of AMF. Moreover, nutrients such as Fe2+, Mg2+ and nitrogen could form a transformation cycle between biochar and fungi, thus improving nutrient use efficiency. Under 150 mmol/L saline-alkali stress, applying a low dose of HA-MBC still played a role in ameliorating soil and mitigating stress, while applying high doses of biochar inhibited the improvement of indicators. This might be due to excessive application of HA-MBC causing surface functional groups to aggregate toxic substances and salt ions excessively and compete for nutrients, subsequently reducing AMF colonization rates, weakening the mycorrhizal symbiosis, and hence diminishing the photosynthetic parameters of muskmelon. [Conclusion] HA-MBC prepared with a biochar to humic acid ratio of 6∶1 and cross-linking time of 72 h, using 0.04 mmol/L FeCl3 and FeSO4 reagents, is suitable for combined application with AMF. The synergistic application of HA-MBC and AMF can improve the physicochemical properties and nutrient structure of saline-alkali soil and promote the photosynthesis of muskmelon under low to medium saline-alkali stress levels, whereas excessive application of HA-MBC under high stress concentrations inhibits the improvement of soil indicators and the recovery of photosynthetic parameters in muskmelon.